Long-term neuropsychiatric and neuropsychological impact of the pandemic in Italian COVID-19 family clusters, including children and parents - Costanza Di Chiara; Martina Ferrarese; Riccardo Boracchini; Anna Cantarutti; Anna Letizia Tibaldo; Chiara Stefanni; Daniele Donà; Marica De Pieri; Alessia Raffagnato; Benedetta Tascini; Marina Miscioscia; Federica Occhino; et al. (PLoS ONE, 2025)
Aim This study investigated the long-term neuropsychiatric and neuropsychological impact of COVID-19 on children and their parents in households with COVID-19 exposure. Methods A prospective cohort study was conducted on 46 families attending the COVID-19 Follow-up Clinic at the Department for Women’s and Children’s Health, Padua (Italy) from December 2021 to November 2022. Self-perceived stress-related, emotional-behavioral, and post-traumatic stress (PTSD-related) symptoms were assessed in both children and parents. Children with underlying neuropsychiatric conditions were excluded from the study. Results A total of 81 parents (median age = 38 years [IQR: 43–48], females = 44 [54.3%]), and 77 children (median age = 8 years [IQR: 5–11], females = 33 [42.9%]) participated in the study. Overall,125 (79%) and 33 (21%) participants were classified as COVID-19 cases and non-COVID-19 cases, respectively. The time interval between the COVID-19 family outbreak and the neuropsychiatric and psychological assessment was ≤4 months (median=3 months [IQR=0]) for 89 (56.3%) participants and >4 months for 69 (43.8%) (median=11.5 months [IQR=5–12]) participants. A total of 136 (86.1%) participants reported stress-related symptoms, with emotional stress being the most common. A positive correlation was observed between self-perceived stress-related symptoms in children and their parents within the same family (r=0.53, p=0.0005). Among children aged 6–18 years, 16 (37.2%) had clinical scores for internalizing symptoms at the Child Behavior Checklist (CBCL), while none children aged 1.5–5 years showed clinical score for internalizing symptoms. Similarly, total difficulty scores at the Strengths and Difficulties Questionnaire (SDQ 4–17) and assessment of PTSD-related symptoms through the Trauma Symptom Checklist for Young Children (TSCYC) questionnaire were within non-clinical cut-offs in 45 (84.9%) and 43 (75.4%) children aged 3–12 years, respectively. The Trauma Symptom Checklist for Children (TSCC) resulted in the non-clinical cut-off for 36 (92.3%) children aged 8–18 years. While a higher prevalence of self-perceived stress-related symptoms was found in COVID-19 cases compared to non-COVID-19 cases (p=.01), no differences were observed for emotional-behavioral and PTSD-related symptoms between the two groups. Conclusions This study documented the impact of the COVID-19 pandemic on Italian children and their family’s stress levels. Further research is needed to confirm our findings and explore the long-term effects of the pandemic on families.